BUDAYA ORGANISASI SEBAGAI PILAR PENGEMBANGAN SUMBER DAYA MANUSIA DI MA AL-KAHFI KOTA BEKASI - Victorynie, Irnie; Sabeni (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyze the organizational culture factors influencing human resource (HR) development at MA Al-Kahfi, Bekasi City. Organizational culture plays a crucial role in shaping a work environment that supports individual and collective growth, particularly in the education sector. The research employed interview methods with management, teachers, and staff as primary informants. The findings indicate that religious values, open communication, and interpersonal collaboration are the main factors in fostering a positive organizational culture. These factors impact the improvement of skills, motivation, and loyalty of HR at MA Al-Kahfi. The study recommends enhancing culture-based training programs and strengthening internal communication to further support HR development.